Performance evaluation of a PEM fuel cell stack with variable inlet flows under simulated driving cycle conditions - Kurnia, J.C. (Elsevier Ltd, 2017)
Alongside battery, polymer electrolyte membrane (PEM) fuel cell stack has been a promising candidate as a power source for hybrid and electric vehicles. On this application, the dynamic performance of the PEM fuel cell is crucial in ensuring smooth operation of the vehicle. The PEM fuel cell stack should be maintained at its optimum performance while being responsive during real road driving condition which is best represented by legislative driving cycle. The present study is conducted to evaluate the performance of a PEM fuel cell stack for vehicle application subjected to New European Driving Cycle (NEDC) by utilizing computational fluid dynamics (CFD) approach. The studied PEM fuel cell stack comprises 320 cells with 1600 cm2 active catalyst area. The effect of variable inlet following NEDC profile on the PEM fuel cell performance is investigated as well. Several possible scenarios, i.e. steady inlet flows, variable inlet flows at anode, cathode, coolant and combinations of these, are examined and discussed in the light of numerical result. The results reveal that variable inlet flows have considerable effect on the total net power generated, thermal envelope and liquid saturation albeit its marginal effects on the stack performance in term of stack power. © 2017